POSSIBILITY OF APPLICATION OF POROUS SILICON AS GLUCOSE BIOSENSOR - G. A. Melikjanyan; Kh. S. Martirosyan
It is well known that any biosensors consists of two basic functional elements: bioselective membranes, using various biological structures such as ferments, antibodies, receptors, living cell, etc., and physical converter of a signal – so-called transducer, which converts chemical signal into electrical one. On the other hand, for the integration of such devices into semiconductor technology it is necessary to utilize widely used semiconductor materials. As is known, silicon is a widely using material in semiconductors industry. So, it will be preferable to utilize the silicon based devices. From this point of view, porous silicon layers may attract the interest aiming the properties of high sensitivity of porous silicon surface to different type external excitations such as gas, light, and especially bioagents.
Keywords: Physics; Materials science